Dynamic balance is impaired after a match in young elite soccer players. (November 2016) - Pau, Massimiliano; Mereu, Federico; Melis, Marco; Leban, Bruno; Corona, Federica; Ibba, Gianfranco
Abstract: Purpose: The aim of this study is to assess the effect of actual match effort on dynamic balance abilities in young elite soccer players. Methods: Seventeen Under 15 male players who compete at national level participated in the study. Their dynamic balance was assessed by having them jump starting with both feet on the ground in a standing position and land on one foot only. Their vertical time to stabilization (vTTS) and postural sway were calculated before and after 35 min of an unofficial match. Postural sway was assessed on the basis of center-of-pressure (COP) trajectories. Parameters considered were sway area, COP displacements in the antero-posterior (AP) and medio-lateral (ML) directions and COP path length. Results: After the match, a significant increase in vTTS (p = 0.007) COP path length (p = 0.001) and COP displacements in ML (p < 0.001) was observed. Such effects involve both non-dominant (vTTS, path length) and dominant limb (COP displacements). Conclusions: The physical effort associated with the match induces significant impairments of players' dynamic balance abilities. On the basis of such findings, coaches might consider integrating training sessions with specific balance exercises as well as performing injury-prevention routines even when players are fatigued, to better adapt them to match conditions. Highlights: We analyzed dynamic balance in young soccer players before and after half match. Dynamic balance was assessed using Time-to-Stabilization (vTTS) and postural sway. After the performance vTTS and postural sway were found significantly higher.